Student's intention to use wikis for Online Collaborative Learning (OCL) - Syed Salim, Sharifah Masitah (2016)
Online Collaborative Learning (OCL) is very prominent nowadays. Even though OCL is utilized all over the globe, there are still limitations in evaluating the factors influencing intention to use tools and technologies of online collaborative learning, especially in Malaysia. This study aimed to investigate factors affecting the intention to use Wikis for OCL through the Unified Theory of Acceptance and Use of Technology (UTAUT) has been adopted in designing the theoretical framework for the study. This framework is applied to examine the significant differences between level of study related to factors affecting the intention to use Wikis namely the performance expectancy, effort expectancy, social influence, the features of OCL and intention to use. A survey was used to collect usable data from 233 undergraduate students in a Universiti Teknologi Malaysia. Structural Equation Modeling (SEM) was used as the technique for data analysis. The results show that all construct was significant predictors of intention to use Wikis. Overall, the proposed model achieves an acceptable fit and explains its variance for 66% of sample. The implications of the study‟s findings for practice and research are discussed, and avenues for future research outlined.